The impact of accounting theoretical courses on students' performance: A case study of the Diploma in Accountancy students, UiTM Sabah - Ebun, Adelina; Hanafiah, Hazlenah; Achil, Mohammad Azlan (2009)
The Diploma in Accountancy is a program which is offered under the Faculty of Accountancy, Universiti Teknologi MARA (UITM). The program is conducted over a period of three years which comprises of six semesters. There are all together thirty four (34) compulsory courses offered throughout the program. For the certification of the Diploma in Accountancy, a student must complete and at least obtain an average grade of "C" for all courses, offered under the program. The courses offered under the program can be grouped as either quantitative or theoretical course. Classification of a particular course as quantitative or theoretical is made by referring to the course content as well as the requirement in the final examination question. Extensive use of numeral or writing in teaching and in designing examination questions are indicators used to determine the quantitative or theoretical status of a particular course. A course that requires students to compute or to provide answer in the form of number is considered as quantitative. On the contrary, a course is considered as theoretical when a student is required to state or discuss on an issue in the form of writing.